Turnover of teachers in compulsory schools in Iceland from 1998 to 2020 - Björnsdóttir, Amalía; Hansen, Börkur (Menntavísindasvið Háskóla Íslands, 2024)
Turnover of teachers is an issue of concern in many countries, and Iceland is no exception (Amalía Björnsdóttir et al., 2019; Amalía Björnsdóttir & Þuríður Jóna Jóhannsdóttir, 2020; Eiríkur Eyjólfsson & Stefán Hrafn Jónsson, 2017; Federičová, 2021). Interest in studying teacher turnover is mainly based on research findings that demonstrate the importance of retaining teachers for sustaining good practices and student learning (Carver-Thomas & Darling-Hammond, 2019; Ronfeldt et al., 2013; Sorensen & Ladd, 2020). According to Grissom et al. (2015) and Nguygen et al. (2020), the main concepts used in these studies are ‘stayers’, ‘movers’, ‘mobility’, and ‘stability’. Generally, studies of turnover compare staff in a given year to the following year, calculating the ratio of stayers or movers, demonstrating mobility or stability during a given time period. Based on the general survey SHARE (Survey of Health, Ageing, and Retirement in Europe) in 19 European countries, teacher turnover is high but varies considerably between countries (Federičová, 2021). The turnover rate trends higher in northern Europe, (e.g., Sweden, Switzerland, and Bulgaria), and lower in southern lands (e.g., Greece, Portugal, and Italy). According to Federičová (2021), the variation between countries is due to different conditions in schooling and labour markets. Carver-Thomas and Darling-Hammond (2019) state that teacher turnover in the United States has been around five per cent for some periods but has been increasing during the past few years and is now around eight per cent. They also say there is considerable variability in teacher turnover between areas, amongst teachers who teach different subjects, and within school characteristics. The shortage of teachers in compulsory schools has been an issue in Iceland for some time now. Eiríkur Eyjólfsson and Stefán Hrafn Jónsson (2017) have noted that this shortage is based on too few university students graduating with teaching certificates as well as too many certified teachers ...